PENGEMBANGAN E-BAHAN AJAR BERBANTUAN AUGMENTED REALITY UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPAS SISWA SD - Tsabita Daffa Adilia; Tri Astuti (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
This research was conducted because the science learning process at SDN Ngadirgo 02 is still dominated by the use of conventional teaching materials, so that student motivation and learning outcomes are not optimal. The research aims to develop e-teaching materials assisted by Augmented Reality (AR) and test its feasibility and effectiveness in improving the motivation and learning outcomes of fourth-grade students on the topic "My Region and Its Natural Resources". The method used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were fourth-grade students of SDN Ngadirgo 02 Semarang. Data collection techniques were carried out through questionnaires, observations, tests and documentation. The data obtained were analyzed using feasibility tests, normality tests, Wilcoxon tests, N-Gain tests. The results of the study showed that the developed AR-assisted e-teaching materials obtained a very feasible category based on expert assessment. This product was also proven effective in improving student motivation and learning outcomes which were in the very high category. Based on these findings, e-teaching materials assisted by Augmented Reality can be a viable and effective innovative alternative to support science learning in elementary schools. ABSTRAK Penelitian ini dilakukan karena proses pembelajaran IPAS di SDN Ngadirgo 02 masih didominasi penggunaan bahan ajar konvensional, sehingga motivasi dan hasil belajar siswa belum optimal. Penelitian bertujuan mengembangkan e-bahan ajar berbantuan Augmented Reality (AR) serta menguji kelayakan dan efektivitasnya dalam meningkatkan motivasi dan hasil belajar siswa kelas IV pada materi “Daerahku dan Kekayaan Alamnya”. Metode yang digunakan adalah Research and Development (R&D) dengan model ADDIE yang meliputi tahap analysis, design, development, implementation, dan evaluation. Subjek penelitian adalah siswa kelas IV SDN Ngadirgo 02 Semarang. Teknik pengumpulan data dilakukan melalui angket, observasi, tes dan dokumentasi. Data yang diperoleh dianalisis menggunakan uji kelayakan, uji normalitas, uji Wilcoxon, serta uji N-Gain. Hasil penelitian menunjukkan bahwa e-bahan ajar berbantuan AR yang dikembangkan memperoleh kategori sangat layak berdasarkan penilaian ahli. Produk ini juga terbukti efektif dalam meningkatkan motivasi dan hasil belajar siswa yang berada pada kategori sangat tinggi. Berdasarkan temuan tersebut, e-bahan ajar berbantuan Augmented Reality dapat menjadi alternatif inovatif yang layak dan efektif untuk mendukung pembelajaran IPAS di sekolah dasar.